RENIN ANGIOTENSIN SYSTEM GENE POLYMORPHISMS IN CHILDREN WITH NEPHROTIC SYNDROM - Zh.P. Sharnova; E.E. Tikhomirova; A.N. Tsygin; V.G. Pinelis (Педиатрическая фармакология, 2006)
To investigate the role of the reninangiotensin system genes polymorphisms in develop and progression of nephrotic syndrom (NS) in children we determined the genotypes of angiotensin converting enzyme (ACE), angiotensinogen (AGT) and angiotensin ii receptor (ATII-R) of 1 type in 80 russian children with ns including and 15 children with chronic renal failure (CRF). Genotype frequencies did not differ between patients with ns and controls (n = 165). The distribution of ace, AGT and ATII-R 1 type genotypes was similar among ns sub groups, such as focal segmental glomerulosclerosis (FSGS) (n = 18), steroid-sensitive nephrotic syndrome (n = 32), nephrotic syndrome with hypertension and hemoturia (n = 22) and with control group. When ns subjects with CRF (n = 15) were compared with control, the prevalence of ace DD genotype was significantly higher (47% VS 21%; χ2 = 4,44; p < 0,05). Our results indicate that the DD genotype ace may be a factor of risk for the dеvеlopment of progressive renal impairment in the children with nephrotic syndrome. The analysis of treatment's effect with inhibitor of ace in groups patients with steroid resistant NS (SRNS) demonstrated decreasing of renoprotective effect of this drugs in patients with id and dd genotypes com? Pared with ii genotype: the degree of blood pressure, proteinuria and the rate of glomerular filtration decrease was significantly lower (55,46 ± 9,25 VS 92,74 ± 25; р < 0,05) in these patients.Key words: nephrotic syndrom, chronic renal failure, polymorphism of genes, renin-angiotensin system.